Refleksi Integrasi Bangsa dalam Pemilu 1999–2024 melalui media interaktif: Studi Mahasiswa Pendidikan Sejarah Universitas Sanata Dharma - Brigida Intan Printina; Anton Haryono (Universitas Galuh, 2025)
This study aims to analyze the critical reflections of History Education students at Sanata Dharma University on the dynamics of national integration in Indonesia’s general elections from 1999 to 2024 through interactive media. The research is grounded in Indonesia’s democratic challenges, including political polarization, identity conflicts, and declining democratic quality. A qualitative approach with a case study design was employed, involving 25 students through observation, interviews, and reflective documentation. The findings reveal that students demonstrate a good understanding of democratic concepts and are able to apply democratic values in daily life. However, challenges remain, such as limited political literacy and low critical awareness of disintegration issues. The study recommends strengthening political education and digital literacy, promoting transparent law enforcement, encouraging inclusive political dialogue, and developing justice-oriented policies to reinforce national integration.